THE ROLE OF KINESITHERAPY AS PREVENTION AND MOTOR CONTROL OF POSTURAL DISORDERS IN ADOLESCENTS - Petya Kasnakova; Biyanka Tornyova; Tanya Paskaleva (Peytchinski Publishing, 2024)
Postural disorders are among the most common musculoskeletal problems of adolescents, which adversely affect their physical and mental development. The purpose of the study is to conduct a screening for the detection of postural disorders and determine the correct approach for correction through a kinesitherapeutic program to improve motor control in case of impaired posture and musculoskeletal imbalance. Material and methods: The study was conducted in 2022-2023 in Plovdiv, 244 adolescents aged between 7 and 18 years, 57.8% (n = 141) girls and 42.2% (n = 103) boys, were studied. Special tests for spinal dysfunctions were applied, and prophylactic measures for neuro-postural remodeling were recommended. Statistical methods were used to illustrate the obtained results. Results: An analysis of the posture was made as a result of the condition of the muscles, fascia, mobility and type of spinal dysfunctions. We found increased thoracic kyphosis in 32.3%, kyphoscoliosis - in 26.2% and lumbar lordosis - in 13.5% of the examined. A kinesitherapy program was drawn up and approved in accordance with the findings of the functional examination. Original rehabilitation algorithms for the prevention of impaired posture have been promoted, including physical exercises for the correction of the deformity, which depends on local factors and is subject to neuro-humoral regulation. Conclusion: Successful prevention and correction of impaired posture depends on early detection establishing the causes, type, degree and severity of the dysfunction. The possible therapeutic approaches and prevention of postural disorders at a young age to overcome spinal deformities with motor activity and targeted kinesitherapy are analyzed.